Epidemiologic and Microbiologic Characteristics of 28 Hospitalized Patients Cocolonized With Multiple Carbapenem-Resistant Enterobacteriaceae (CRE) in the United States. (October 2020) - Adediran, Timileyin; Harris, Anthony; Johnson, J. Kristie; Calfee, David; Miller, Loren; Nguyen, Minh-Hong; Goodman, Katherine; Pineles, Lisa
Abstract : Background: As carbapenem-resistant Enterobacteriaceae (CRE) prevalence increases in the United States, the risk of cocolonization with multiple CRE may also be increasing, with unknown clinical and epidemiological significance. In this study, we aimed to describe the epidemiologic and microbiologic characteristics of inpatients cocolonized with multiple CRE. Methods: We conducted a secondary analysis of a large, multicenter prospective cohort study evaluating risk factors for CRE transmission to healthcare personnel gown and gloves. Patients were identified between January 2016 and June 2019 from 4 states. Patients enrolled in the study had a clinical or surveillance culture positive for CRE within 7 days of enrollment. We collected and cultured samples from the following sites from each CRE-colonized patient: stool, perianal area, and skin. A modified carbapenem inactivation method (mCIM) was used to detect the presence or absence of carbapenemase(s). EDTA-modified CIM (eCIM) was used to differentiate between serine and metal-dependent carbapenemases. Results: Of the 313 CRE-colonized patients enrolled in the study, 28 (8.9%) were cocolonized with at least 2 different CRE. Additionally, 3 patients were cocolonized with >2 different CRE (1.0%). Of the 28 patients, 19 (67.6%) were enrolled with positive clinical cultures. Table 1 summarizes the demographic and clinical characteristics of these patients. The most frequently used antibiotic prior to positive culture was vancomycin (n = 33, 18.3%). Among the 62 isolates from 59 samples from 28 patients cocolonized patients, the most common CRE species were Klebsiella pneumoniae (n = 18, 29.0%), Escherichia coli (n = 10, 16.1%), and Enterobacter cloacae (n = 9, 14.5%). Of the 62 isolates, 38 (61.3%) were mCIM positive and 8 (12.9%) were eCIM positive. Of the 38 mCIM-positive isolates, 33 (86.8%) were KPC positive, 4 (10.5%) were NDM positive, and 1 (2.6%) was negative for both KPC and NDM. Also, 2 E. coli, 1 K. pneumoniae, and 1 E. cloacae were NDM-producing CRE. Conclusion: Cocolonization with multiple CRE occurs frequently in the acute-care setting. Characterizing patients with CRE cocolonization may be important to informing infection control practices and interventions to limit the spread of these organisms, but further study is needed. Funding: None Disclosures: None